Satisfaction Analysis of the Google Classroom Use in the application of E-Learning with the Technology Acceptance Model (TAM) approach among High School students - Kristia Chris Yuliawan (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
In carrying out learning at home, students must be assisted with online learning applications or e-learning lessons. E-learning is a type of teaching and learning that allows the delivery of teaching materials to students using the internet or other computer network media. One of the applications used in e-learning is Google Classroom. This research takes a case study at Anak Panah Christian High School, Nabire Regency. This study focuses on analyzing the level of student satisfaction in using the Google Classroom application by analyzing it using the Technology Acceptance Model (TAM) using five variables, namely Perceived Ease of Use (PEU), Perceived Usefulness (PU), Attitude Toward Using (ATU). Behavioural Intention (BI) and Actual Usage (AU). The hypothesis in connecting these variables in this study uses the Structural Equation Model (SEM) through the Partial Least Structural (PLS) approach using the SmartPLS application. The results of the research shows that all the variables used have positive values that indicate the level of student satisfaction with the use of Google Classroom in e-learning learning in schools, but the ease of use of the Google Classroom application does not affect the attitudes and behaviour of students in increasing students' interest or intention in learning.